Pengembangan Hermeneutika Schleiemacher Di Dalam Memahami Matius 12:31-32 - Samuel Lengkong (EUANGGELION: Jurnal Teologi dan Pendidikan Kristen, 2022)
In the history of the development of the Pentecostal and Charismatic churches there are a number of people who see the phenomena of the manifestation and infilling of the Holy Spirit mocking, laughing, insulting, and even saying heresy as the work of Satan. However, there are a number of testimonies for those who make fun of, laugh at, insult, and even say heresy as the work of Satan on the phenomena of the manifestation and infilling of the Holy Spirit to be faithful and truly in God, even receiving the fullness of the Holy Spirit. This paper aims to find the true meaning and understand Matthew 12:31-32 based on Friedrich D. E. Schleiemacher's parallelization and romantic approach to hermeneutics, so as to gain a valid and highly anticipatory understanding in the life of Christian faith. The qualitative research method used by the researcher is library research. The result of this study is that as a defense, Jesus challenged the Pharisees that if Jesus used the power of Satan in the name of the power of the Spirit of God, it meant that Jesus was blaspheming the Holy Spirit, then Jesus was ready not to be forgiven. The difference regarding the sin against the Son of Man will be forgiven, but the sin against the Holy Spirit will not be forgiven, does not indicate that there is a difference in degree between the Son of Man and the Holy Spirit. However, the difference lies in the nature of humans themselves, namely humans who are basically "evil"